2022
DOI: 10.1021/acs.jproteome.2c00299
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica Cathepsin L Zymogens: Immuno-Proteomic Evidence for Highly Immunogenic Zymogen-Specific Conformational Epitopes to Support Diagnostics Development

Abstract: Fasciola hepatica, the common liver fluke and causative agent of zoonotic fasciolosis, impacts on food security with global economic losses of over $3.2 BN per annum through deterioration of animal health, productivity losses, and livestock death and is also re-emerging as a foodborne human disease. Cathepsin proteases present a major vaccine and diagnostic target of the F. hepatica excretory/secretory (ES) proteome, but utilization in diagnostics of the highly antigenic zymogen stage of these proteins is surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In a more recent study, proteomic analyses revealed that the recombinant and native cathepsin L zymogens contain conserved, highly antigenic epitopes that are conformationally dependent. Additionally, the diagnostic capacities of cathepsin L zymogens were confirmed using serum and fecal panel of samples, suggesting an excellent efficacy as markers of infection and for monitoring treatment efficacy ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, proteomic analyses revealed that the recombinant and native cathepsin L zymogens contain conserved, highly antigenic epitopes that are conformationally dependent. Additionally, the diagnostic capacities of cathepsin L zymogens were confirmed using serum and fecal panel of samples, suggesting an excellent efficacy as markers of infection and for monitoring treatment efficacy ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are suitable for use in a variety of situations. Cysteine protease and glutathione S transferase [7] have been used to detect F. hepatica infection, including commercially available kits from TSZ bio and Ildana Biotech [8]. However, most methods focus on antibodies and research on antigen detection is limited.…”
mentioning
confidence: 99%